(untitled) (Revista Brasileira de Pesquisa em Saúde/Brazilian Journal of Health Research, 2025)
The choice of the most appropriate study design in clinical research should not be reduced to a rigid hierarchy of evidence. While Randomized Clinical Trials (RCTs) are often considered the gold standard, their superiority over observational studies depends on the research question, ethical considerations, feasibility, and clinical context. Well-designed observational studies can yield results consistent with RCTs and are especially valuable for investigating prognosis, incidence, prevalence, and long-term safety in real-world practice. Conversely, RCTs provide strong internal validity but may lack external applicability due to strict eligibility criteria. In several fields — such as rehabilitation, palliative care, mental health, and rare diseases — RCTs face practical and ethical limitations, reinforcing the role of observational research. Ultimately, the reliability of evidence depends less on the study label than on methodological rigor, validity, and applicability. Rather than debating superiority, RCTs and observational studies should be seen as complementary approaches that, together, strengthen clinical decision-making.